A systematic literature review on ecological discourse analysis (2014–2023) - Song Xu; Bakar Kesumawati A.; Abas Azlan; Wan Abdul Halim Wan Fatimah Solihah (Journal of World Languages, 2025)
Ecological discourse analysis (EDA) has sparked growing attention in ecolinguistics. To reveal the status and trend of EDA (2014–2023), this research conducts a systematic literature review (SLR) on this topic, employing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement as the established standard. After analysis, the SLR revealed that the number of EDA increased significantly between 2014 and 2023. Notably, Chinese scholars demonstrated the greatest focus on this topic. While EDA was widespread across various countries, international collaboration still needs to be enhanced. Meanwhile, some scholars tended to conduct EDA by adopting multiple research approaches. This SLR also unveiled the latest focuses on EDA, such as the language and its relationship with ecosophy, the ecological influence of discourses, the noteworthy topics of climate change and children’s literature, and the gap of the study on video discourse. This enables the employment of multimodal discourse research and interdisciplinary approaches for EDA to be the future trend. Since this SLR gives a comprehensive description of the trajectory of EDA, it can offer a meaningful reference for the studies relating to EDA in the linguistics domain.